Cause of Upper Gastrointestinal Tract Bleeding in Dengue Hemorrhagic Fever Patient - Elza Febria Sari; Ari Fahrial Syam; Leonard Nainggolan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2008)
Dengue fever is an acute mosquito-transmitted disease caused by the dengue fever virus which had clinical manifestations range from fever to severe hemorrhage, shock, and death.1  There were 500,000 cases of dengue hemorrhagic fever and 25,000 deaths due to dengue annually worldwide. Bleeding is one of the major problems encountered in dengue fever. The reported prevalence of upper gastrointestinal bleeding in dengue patients varies from 5% to 30%. The pathogenesis of hemorrhage could be multifactor and include vasculopathy, platelet deficiency, and dysfunction, and blood coagulation defects. We presented here a case of 27 years-old male patient who had clinical manifestation of hematemesis on his third day of fever.   Keywords: GI tract, bleeding, DHF